The influence of camouflage and prey type on predatory decisions of jumping spider - Bartos, Maciej (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2013)
Decisions made by predators during predatory encounters are often based on multiple factors that may influence the outcome of the encounters. For stalking predators their visibility to the prey and the ability of their prey to escape may be important factors influencing predatory success. Hence they are likely to adapt their predatory behavior when approaching prey on backgrounds with different camouflaging properties, but only if the prey is able to escape. To test whether jumping spiders flexibly adapt their predatory behavior to camouflaging properties of the background and prey type, the behavior of Yllenus arenarius (Araneae, Salticide), a cryptically colored jumping spider hunting leafhoppers (high escape potential) and caterpillars (low escape potential) on two types of background: matching and non-matching for the spiders was analyzed. Background color had a significant effect on the spiders’ jumping distance and their predatory success, but only if the prey had a high escape potential. No differences occurred between backgrounds if the prey could not escape. On camouflaging background the spiders attacked leafhoppers from a shorter distance and had a higher success than on non-camouflaging background.